IDENTITY CONSTRUCTION AND CULTURAL VALUES IN THE SCREENPLAY OF ZATHURA: A SPACE ADVENTURE (2005) - Aidelwaiss Ulfatul Kamilah; Arsyi Azwar; Jasmine Flora Nirwana (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2026)
This study examines Zathura: A Space Adventure (2005), based on the screenplay by David Koepp, as a work of popular literature that grounds a fantastical cosmic journey in the